Access to oral health services of children and adolescents with disabilities in a large municipality in Northeast Brazil (Research, Society and Development, 2021)
Objective: To identify access to oral health services and difficulties in dental care for children and adolescents with disabilities, institutionalized, in Campina Grande, PB. Methods: An observational, descriptive, quantitative, cross-sectional study was conducted with caregivers of children and adolescents with disabilities, who attended the APAE-CG. The data were analyzed using techniques of descriptive statistics by absolute and percentage distributions. Results: It was observed that 64.6% of children and adolescents had already been taken to the Dentist, with the most sought service being the Family Health Strategy (FHS) (58.0%). 67.9% stated that they did not find access difficulties. Among those who reported having difficulty, the main complaint referred to the FHS professional's refusal to treat patients with disabilities (52.9%). Conclusion: Most children and adolescents, users of APAE-CG, had already been taken to the Dentist. The main complaint regarding non-attendance, referred to the refusal of the ESF professionals.